2008
DOI: 10.1186/1471-2180-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonal dynamics of bacterial community in indoor environment

Abstract: Background: We spend most of our lives in indoor environments and are exposed to microbes present in these environments. Hence, knowledge about this exposure is important for understanding how it impacts on human health. However, the bacterial flora in indoor environments has been only fragmentarily explored and mostly using culture methods. The application of molecular methods previously utilised in other environments has resulted in a substantial increase in our awareness of microbial diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
244
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(277 citation statements)
references
References 51 publications
(57 reference statements)
25
244
4
3
Order By: Relevance
“…It cannot be excluded that some of the phylotypes reported here are due to the transient microorganisms. Recent cultureindependent studies on indoor environments, specifically house dust (Rintala et al, 2008) have indicated a complex community dominated by Gram-positive taxa, including members of the genera Corynebacterium, Propionibacterium, Staphylococcus and Streptococcus (Täubel et al, 2009), supporting a permanent source of inoculation for the nose. A total of 15 sequences from five of six volunteers not included in our bacterial diversity analysis supported the presence of chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be excluded that some of the phylotypes reported here are due to the transient microorganisms. Recent cultureindependent studies on indoor environments, specifically house dust (Rintala et al, 2008) have indicated a complex community dominated by Gram-positive taxa, including members of the genera Corynebacterium, Propionibacterium, Staphylococcus and Streptococcus (Täubel et al, 2009), supporting a permanent source of inoculation for the nose. A total of 15 sequences from five of six volunteers not included in our bacterial diversity analysis supported the presence of chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Though verified on evidence and useful in routine identification in clinical laboratories (Lau et al, 2006;Woo et al, 2003), the commercial database might be unsuitable for identification of novel sequences (Fontana et al, 2005). S. pettenkoferi has been shown to be present in the indoor environment by direct analysis of the 16S rRNA gene from settled dust samples (Rintala et al, 2008). Our isolates were found to have more than 99 % similarity with these samples from indoor dust (accession no.…”
Section: Discussionmentioning
confidence: 98%
“…Faith et al (2009) presented an example documenting unimodal response of branches based on a gradient space for microbial communities, sampled in house dust ( Fig. 2; Rintala et al 2008). In Fig.…”
Section: How the Ed Methods Converts Pd-dissimilarities To Estimates Omentioning
confidence: 99%
“…The solid dots in the space indicate different communities or sample localities. A sample locality represents the branch corresponding to a given family if the locality has one or more descendants of that branch in the phylogeny (for details see Rintala et al 2008;Faith et al 2009). …”
Section: How the Ed Methods Converts Pd-dissimilarities To Estimates Omentioning
confidence: 99%
See 1 more Smart Citation